Korovkin type approximation theorem for functions of two variables via statistical summability (C, 1) - Mursaleen, Mohammad; Mohiuddine, Syed Abdul (Acta Scientiarum. Technology, 2015)
The concept of statistical summability (C, 1) has recently been introduced by Moricz (2002). In this paper, we use this notion of summability to prove the Korovkin type approximation theorem for functions of two variables. Finally we construct an example by Bleimann, Butzer and Hahn operators to show that our result is stronger than those of previously proved by other authors for ordinary convergence and statistical convergence. Â 